Consumer Behaviour Dimensions in Selection of Undergraduate Management Specialization Courses in Nepal - Shrestha, Shankar Kumar; Shrestha, Bikash (Nepal Journal of Mathematical Sciences, 2021)
Tribhuvan University has designed their undergraduate BBA program by offering students the possibility to customize their educational program through the specialization in four different areas: banking & finance, industry and services management, micro enterprise management, and sales and marketing management. However, students have been specializing only in two courses namely: banking & finance, and sales and marketing. In this regard, the study aims at understanding the specialization choice of such students, as marketers need to be more aware of the underlying factors considered by students when choosing specialization and design the product offerings in this competitive market. The study has the objective of examining the effect of various decision-making variables on the specialization choice of undergraduate students from a consumer behavior perspective.